202k views
5 votes
Simplify the expression below then match them to the appropriate answer.

Simplify the expression below then match them to the appropriate answer.-example-1

1 Answer

6 votes

The given expression as;

a)


\begin{gathered} \sqrt[]{-1024}=\sqrt[]{-1}\sqrt[]{1024} \\ \text{ SInce, }1024=32*32 \\ 1024=32^2 \\ \sqrt[]{-1024}=\sqrt[]{-1}\sqrt[]{32^2} \\ \sqrt[]{-1024}=32i \end{gathered}

b)


\begin{gathered} (5i)(2i)=5*2i* i \\ (5i)(2i)=10i^2 \\ As,i^2=-1 \\ \mleft(5i\mright)\mleft(2i\mright)=-10 \end{gathered}

c)


\begin{gathered} \sqrt[]{-100}=\sqrt[]{-1}\sqrt[]{100} \\ As,\sqrt[]{-1}=i\text{ and }\sqrt[]{100}=\sqrt[]{10^2}=10 \\ \sqrt[]{-100}=\sqrt[]{-1}\sqrt[]{100} \\ \sqrt[]{-100}=10i \end{gathered}

d)


\begin{gathered} (4i)^2(2i)=(4^2i^2)(2i) \\ \text{ Since, i}^2=-1 \\ (4i)^2(2i)=4*4(-1)2i \\ (4i)^2(2i)=-16(2i) \\ (4i)^2(2i)=-32i \end{gathered}

...

User Patrick Connors
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.